Similar Seed Composition Phenotypes Are Observed From CRISPR-Generated In-Frame and Knockout Alleles of a Soybean KASI Ortholog - Virdi, Kamaldeep S.; Spencer, Madison; Stec, Adrian O.; Xiong, Yer; Merry, Ryan; Muehlbauer, Gary J.; Stupar, Robert M. (Frontiers in Plant Science, 2020)
The β-ketoacyl-[acyl carrier protein] synthase 1 (KASI) gene has been shown in model plant systems to be critical for the conversion of sucrose to oil. A previous study characterized the morphological and seed composition phenotypes associated with a reciprocal chromosomal translocation that disrupted one of the KASI genes in soybean. The principle findings of this work included a wrinkled seed phenotype, an increase in seed sucrose, a decrease in seed oil, and a low frequency of transmission of the translocation. However, it remained unclear which, if any, of these phenotypes were directly caused by the loss of KASI gene function, as opposed to the chromosomal translocation or other associated factors. In this study, CRISPR/Cas9 mutagenesis was used to generate multiple knockout alleles for this gene, and also one in-frame allele. These soybean plants were evaluated for morphology, seed composition traits, and genetic transmission. Our results indicate that the CRISPR/Cas9 mutants exhibited the same phenotypes as the chromosomal translocation mutant, validating that the observed phenotypes are caused by the loss of gene function. Furthermore, the plants harboring homozygous in-frame mutations exhibited similar phenotypes compared to the plants harboring homozygous knockout mutations. This result indicates that the amino acids lost in the in-frame mutant are essential for proper gene function. In-frame edits for this gene may need to target less essential and/or evolutionarily conserved domains in order to generate novel seed composition phenotypes.